Impact of Animal Assisted Therapy on Anxiety Levels Among Mentally Ill Female Inmates. Issue 4 (1st October 2020) - Holman, Leigh Falls; Wilkerson, Shelly; Ellmo, Frances; Skirius, Michael
ABSTRACT: There are now more women with serious mental illness treated in correctional facilities than in county or state hospitals in the United States. These women have high rates of relational trauma, resulting in post-traumatic stress and other anxiety disorders, at a higher rate those in the community. In addition, the prison setting serves as a trigger for anxiety symptoms. Existing treatment outcome studies primarily focus on male prisoners or interventions in community settings. Therefore, a need for gender-specific, trauma-informed interventions in prison settings exists. The current study is a single-case, repeated measures experimental design exploring the impact of an animal-assisted therapy intervention on levels of anxiety among women incarcerated in a prison mental health unit. The study demonstrates moderate to high effect sizes for women with significant pre-treatment anxiety.